2018
DOI: 10.3389/fvets.2018.00247
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of the Milk Microbiota of Healthy and Inflamed Bovine Mammary Glands From Dryoff Through 150 Days in Milk

Abstract: The objective of this longitudinal cohort study was to describe the milk microbiota of dairy cow mammary glands based on inflammation status before and after the dry period. Individual mammary quarters were assigned to cohorts based on culture results and somatic cell count (SCC) at dryoff and twice in the first 2 weeks post-calving. Mammary glands that were microbiologically negative and had low SCC (< 100,000 cells/mL) at all 3 sampling periods were classified as Healthy (n = 80). Microbiologically negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 48 publications
9
46
4
Order By: Relevance
“…The proportion of culture-negative cases was similar to those reported by Pinzón-Sánchez and Olde Riekerink et al (2008). Failure to recover pathogens from milk samples collected from cases of CM include spontaneous bacteriological clearance be-fore detection of inflammation (Smith et al, 1985;de Haas et al, 2002), occurrence of false-negative microbiological results (Silva et al, 2005;Lago, 2009), or mastitis caused by a nonculturable bacteria (Metzger, 2018). Occurrence of spontaneous cure is often evident based on rapid resolution of QSCC after resolution of clinical signs; in one study, SCC of culture-negative cases returned to almost-normal values 21 to 28 d after case detection (de Haas et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…The proportion of culture-negative cases was similar to those reported by Pinzón-Sánchez and Olde Riekerink et al (2008). Failure to recover pathogens from milk samples collected from cases of CM include spontaneous bacteriological clearance be-fore detection of inflammation (Smith et al, 1985;de Haas et al, 2002), occurrence of false-negative microbiological results (Silva et al, 2005;Lago, 2009), or mastitis caused by a nonculturable bacteria (Metzger, 2018). Occurrence of spontaneous cure is often evident based on rapid resolution of QSCC after resolution of clinical signs; in one study, SCC of culture-negative cases returned to almost-normal values 21 to 28 d after case detection (de Haas et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Evidence has shown that cow mastitis-associated pathogens such as Streptococcus uberis, although present in small quantities, are part of the normal milk microbiota; thus, the development of mastitis may be a dysbiosis of milk microbiota rather than a simple primary infection [37,38] . Others suggested that the microbiota community in milk is relevant to in ammation status and showed that the bacterial ora are more abundant but less diverse in milk of cows suffering from in ammation [39]. In the present study, we found that elevated the abundance of Stenotrophomonas in rumen was associated with mastitis during cows suffering SARA.…”
Section: Discussionsupporting
confidence: 58%
“…The most common taxa found in the quarter milk samples are frequently reported in previous milk microbiota studies 2 , 20 . The family Corynebacteriaceae , which includes only the genus Corynebacterium, has been previously described as part of the skin-associated microbiome in humans and it is also found in other bovine body sites, such as the teat canal and uterus 24 27 .…”
Section: Discussionsupporting
confidence: 52%
“…These included Aerococcaceae , families within the order Clostridiales, Streptococcaceae and Enterococcaceae. The sampling regime used in the study resulted in a similar or lower bacterial richness in our samples compared to previous studies 20 22 . However, comparisons with other studies cannot be conclusive due to different sampling procedures, filters and bioinformatics pipelines used between the studies.…”
Section: Discussionmentioning
confidence: 50%